The Relationship Between Pregnancy Interval and Family Support With The Incidence of Emesis Gravidarum in First Trimester Pregnant Women - Nurul Laili Purnomo; Sulistiyah Sulistiyah (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
Emesis gravidarum is a common condition experienced by pregnant women during the first trimester and can negatively affect maternal comfort, nutritional intake, and overall pregnancy well-being. Various biological and psychosocial factors are believed to influence its occurrence, including pregnancy interval and the level of family support. This study aimed to analyze the relationship between pregnancy interval and family support with the incidence emesis gravidarum among first-trimester pregnant women. A quantitative analytic study with cross-sectional design was conducted involving 30 pregnant women in their first trimester. Data were collected using structured questionnaires to assess pregnancy interval, family support (emotional, informational, instrumental, and appraisal support), and the incidence of emesis gravidarum. Statistical analysis was performed using SPSS, including univariate analysis to describe respondent characteristics and bivariate analysis using the Chi-square test to determine the relationships between variables, with a significance level set at p < 0.05. The results showed that short pregnancy intervals were significantly associated with a higher incidence of emesis gravidarum. In addition, pregnant women who reported low levels of family support were more likely experience moderate severe emesis gravidarum compared to those receiving adequate support. Statistical testing confirmed that both pregnancy interval and family support had significant relationship with the occurrence of emesis gravidarum. In conclusion, pregnancy interval and family support are important factors influencing the incidence of emesis gravidarum in the first trimester. Strengthening family involvement and promoting optimal pregnancy spacing are recommended as part of comprehensive antenatal care to reduce pregnancy discomforts and improve maternal health outcomes.